L’inflation canadienne de la dernière décennie vue à travers CANDIDE - Bodkin, Ronald; Sheikh, Munir; Chabot-Plante, Francine (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
AbstractIn this paper, a large scale econometric model of the Canadian economy (CANDIDE) is employed to study questions concerning the evolution of Canadian prices over the period 1960-1974. After a brief description of the wage-price sectors of the model, "trade-off" or Phillips curves are derived on the basis of simulations of the entire model, for the periods 1960-1965 and 1965-1970 separately. On the basis of these simulations, it is found that the trade-off curve does not appear to be very sensitive to the choice of the instrument utilized to move the Canadian economy from positions of lower to fuller utilization of its labour resources. The position of the curve is, however, quite sensitive to the rate of increase of U.S. prices; also, the full curve appears to have shifted upward considerably from the first to the second subperiod. The analysis of the period 1970-1974 suggests, among other conclusions, the possibility that an even rate of U.S. inflation over this period of rather violent fluctuations in U.S. prices could have had in itself favourable repercussions on the Canadian trade-off curve. The concluding section presents another summary of the major findings, as well as some important caveats and qualifications.